Insights into structure and function of 30S Ribosomal Protein S2 (30S2) in Chlamydophila pneumoniae: A potent target of pneumonia. (February 2017) - Koteswara Reddy, G.; Nagamalleswara Rao, K.; Yarrakula, Kiran
Graphical abstract: Highlights: The protein 30S2 structure was modelled and validated by Ramachandran plot. Modelled protein has under most favoured "core" region to be found 88.7%. Modelled protein has an overall average score −0.20 obtained by G-factor statistics. Seven sequence motifs have been identified for 30S2 with reference codes ( PR0095, PF0038, TI GR 01012, PTHR11489, SSF52313 and PTHR11489 ) . Seven structural highly conserved residues have been identified in the cleft with large volume 1288.83 Å 3 and average depth of the cleft is 10.75 Å. Abstract: The gene 30S ribosomal protein S2 ( 30S2 ) is identified as a potential drug and vaccine target for Pneumonia. Its structural characterization is an important to understand the mechanism of action for identifying its receptor and/or other binding partners. The comparative genomics and proteomics studies are useful for structural characterization of 30S2 in C. Pneumoniae using different bioinformatics tools and web servers. In this study, the protein 30S2 structure was modelled and validated by Ramachandran plot. It is found that the modelled protein under most favoured "core" region was 88.7% and overall G-factor statistics with average score was −0.20. However, seven sequential motifs have been identified for 30S2 with reference codes ( PR0095, PF0038, TIGR01012, PTHR11489, SSF52313 and PTHR11489). In addition, seven structural highly conserved residues have been identified in the large cleft are Lys160, Gly161 and Arg162 with volume 1288.83 Å 3 and average depth of the cleft was 10.75 Å. Moreover, biological functions, biochemical process and structural constituents of ribosome are also explored. The study will be helped us to understand the sequential, structural, functional and evolutionary clues of unknown proteins available in C. Pneumoniae.